2016
DOI: 10.2134/jeq2015.06.0321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Riparian Buffer Vegetation and Width: A 12‐Year Longitudinal Study

Abstract: Agricultural contributions of nitrogen are a serious concern for many water resources and have spurred the implementation of riparian buffer zones to reduce groundwater nitrate (NO 3 ). The optimum design for buffers is subject to debate, and there are few long-term studies. The objective of this project was to determine the effectiveness over time (12 yr) of buffer types (trees, switchgrass, fescue, native, and a control) and buffer widths (8 and 15 m) by measuring groundwater NO 3 -N and dissolved organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Areas adjacent to watercourse are assumed to play a key role in C dynamics mainly due to the influence of hydrologic regimes and riparian vegetation which: 1) controls import/export OM fluxes between the watercourse and the floodplain, 2) creates fluctuations of anaerobic/aerobic conditions regulating C source/sink balance, and 3) encourages more diverse microbial communities (Camino-Serrano et al 2016; Gurtz et al 1988; King et al 2016; Lewis et al 2003). However, as far as soil physicochemical properties are concerned, our results disagree with the general assumption of more potential for C storage within the riparian zone.…”
Section: Discussionmentioning
confidence: 99%
“…Areas adjacent to watercourse are assumed to play a key role in C dynamics mainly due to the influence of hydrologic regimes and riparian vegetation which: 1) controls import/export OM fluxes between the watercourse and the floodplain, 2) creates fluctuations of anaerobic/aerobic conditions regulating C source/sink balance, and 3) encourages more diverse microbial communities (Camino-Serrano et al 2016; Gurtz et al 1988; King et al 2016; Lewis et al 2003). However, as far as soil physicochemical properties are concerned, our results disagree with the general assumption of more potential for C storage within the riparian zone.…”
Section: Discussionmentioning
confidence: 99%
“…5). Buffer width was positively related to N and P retention (Dosskey, 2001;Feld et al, 2011;Sweeney & Newbold, 2014;King et al, 2016) and, together with buffer zonation, they can control the amount of nutrients retained from surface runoff and upper groundwater…”
Section: Nutrient Pollutionmentioning
confidence: 99%
“…A buffer width of 30 m was reported to effectively retain N and P from surface and sub-surface groundwater runoff, if buffers consisted of multiple zones of mature wooded vegetation and grass strips (Feld et al, 2011;Sweeney & Newbold 2014). King et al (2016) found that 15 m wide buffers retained 2.5 times more nitrogen from the sub-surface groundwater than 8 m wide buffers, while buffer vegetation type had no significant effect.…”
Section: Nutrient Pollutionmentioning
confidence: 99%
“…Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017). Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017).…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%
“…Assessing benefits of agricultural BMPs is challenging due to the multiple impacts on hydrology, nutrient cycling, soil fertility, and other processes. Previous studies have largely focused on assessment of BMP performance in reducing nutrient and sediment loss and the subsequent impacts on water quality (Parajuli et al 2013;Weissteiner et al 2013;Kladivko et al 2014;Yeo et al 2014;McLellan et al 2015;King et al 2016;Merriman et al 2018) (see also study reviews in Hashemi et al 2016;Liu et al 2017). BMPs that slow runoff are effective in reducing sediment detachment and transport (Bosch et al 2013;Mitchell et al 2018), although effectiveness can vary depending on watersheds characteristics, BMPs location, and storm magnitude.…”
Section: Agricultural Practices and Flood Impactsmentioning
confidence: 99%